2020
DOI: 10.3390/ijerph17176179
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Health-Led Cognitive Behavioral-Based Group Therapy on Pain, Functional Disability and Psychological Outcomes among Knee Osteoarthritis Patients in Malaysia

Abstract: Background: Psychosocial interventions for patients with osteoarthritis (OA) of the knee to reduce pain and improve physical and psychological functioning are still lacking in Malaysia. Methods: A parallel-group unblinded randomized controlled trial involving 300 patients was conducted in two hospital orthopedics clinics in Malaysia. Patients were randomly assigned to receive cognitive behavioral-based group therapy (n = 150) or no further intervention (n = 150). The primary outcome was the change from baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Study participants were recruited in US [ 39 , 40 ], Malaysia [ 41 ], France [ 42 ], Finland [ 43 ], and Hong Kong [ 37 , 38 ]. To include study participants, four studies confirmed radiographic knee OA [ 39 41 , 43 ], and three studies used American College of Rheumatology clinical criteria [ 37 , 38 , 42 ]. Sample sizes in the selected studies ranged between 80 [ 39 ] and 300 [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Study participants were recruited in US [ 39 , 40 ], Malaysia [ 41 ], France [ 42 ], Finland [ 43 ], and Hong Kong [ 37 , 38 ]. To include study participants, four studies confirmed radiographic knee OA [ 39 41 , 43 ], and three studies used American College of Rheumatology clinical criteria [ 37 , 38 , 42 ]. Sample sizes in the selected studies ranged between 80 [ 39 ] and 300 [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Provided programme for comparison arms of interventions in each of the included studies are shown in Additional file 2 . Two studies provided conventional orthopaedic intervention [ 38 , 39 ], and the other two studies provided standard care (including education booklet) [ 41 , 42 ]. Exercise programme [ 40 ], spa therapy and education booklet [ 43 ], and ordinary general practioner’s (GP) care were also provided.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations